Pregnancy and delivery in women over 35 years old - Kubiak-Fortecka, Agnieszka; Wilczyński, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
Women in the twenty-first century play a more active role in social and working life. They strive to achieve an adequate education and material status and postpone motherhood. Therefore more and more women over 35 years of age become mothers. Thanks to techniques of assisted reproduction it is possible. However, we have to keep in mind that pregnancy in mature women is not so risky because of the age, but may be associated with various complications. In pregnant women over the age of 35 there are statistically more cases of intrauterine fetal death, miscarriage, genetic defects, hypertension, gestational diabetes and preterm deliveries. These pregnancies are usually completed by caesarean section because of elective indications. Children of women over the age of 35 are usually born in a good condition, as measured both on the Apgar scale and by the cord blood pH. Despite the fact that pregnancy in mature women can cause medical complications such as hypertension or gestational diabetes, with properly conducted perinatal care it does not raise any reservations and, what is more, the results are comparable with younger women.